Tuesday

January 27, 2015

January 27, 2015

Posted by **christy** on Friday, April 8, 2011 at 3:03pm.

he can find a similar equation for

Examine his argument. If it is correct, supply any missing

steps or justifications; if it is incorrect, point out why.

= a2 - 2ab + b2

= a2 + 2a1-b2 + 1-b22

1a - b22 = 3a + 1-b242

2ab + b2, 1a - b22.

1a + b22 = a2 +

**Answer this Question**

**Related Questions**

math - Kahlil said that using the equation € (a + b)2 = a2 + 2ab + b2, , he can ...

math - Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find...

math - Hosni gave the following argument that -(a+b)=-a+-b for all integers a ...

Math - Hosni gave the following argument that -(a + b) = -a + -b, for all ...

math - 42. Hosni gave the following argument that 2(a 1 b) 5 2a 1 2b, for all ...

algebra - Hosni gave the following argument that 2(a 1 b) 5 2a 1 2b, for all ...

calculus help - find the producer's surplus at a price level of p=$150 for the ...

algebra,help - I am clueless about this one...can someone help me with it ......

Logic - Supply steps in a proof of a valid argument and give reasons using rules...

Algebra ?? - What would be the missing piece of information given the following ...